Effect of IAA on in vitro growth and colonization of Nostoc in plant roots - Hussain, Anwar; Shah, Syed T.; Rahman, Hazir; Irshad, Muhammad; Iqbal, Amjad (Frontiers in Plant Science, 2015)
Nostoc is widely known for its ability to ﬁx atmospheric nitrogen, and undergoes symbiotic references with plants from wide taxonomic groups. Several strains of Nostoc produce phytohormones and promote growth of its partners. Nostoc OS-1 was selected for its ability to produce Indole-3-acetic acid (IAA) and the presence of putative ipdC gene responsible for the production of a key enzyme of IAA biosynthesis pathway. The amount of cellular and released IAA was determined by UPLC-ESI-MS/MS. Amount of IAA (released as well as cellular) increased with prolonging incubation time and reached to the peak at the third week (21 pmol mg-1 Ch-a). Interestingly, the strain efficiently colonized the roots of rice as well as wheat under axenic conditions. Induction of ipdC gene in Nostoc upon root colonization suggested the possible involvement of IAA in the event. To evaluate the impact of IAA on root colonization efficiency of this strain, an ipdC knockout mutant in the background of Nostoc was generated by homologous recombination method. The knockout mutant could release only 13% of the normal IAA. Association of the mutant and wild type strain with rice and wheat roots was studied under axenic conditions. Signiﬁcant reduction (P < 0.05) in the root colonization efficiency of ipdC mutant was demonstrated by low chlorophyll-a concentration in the roots associated with such strains. By contrast, wild type strain was not only better root colonizer but also enhanced growth of rice and wheat under axenic conditions. It may be concluded that Nostoc sp. OS-1 uses IAA as a tool of root colonization